The Influence of the Implementation of School Quality Management System Factors on Teachers’ Work Motivation - Zainullah, Zainullah; Bashori , Abdul Hamid; Nurrita, Teni; Rahayu, Sri Rohwahyuti; Priyudahari, Bhujangga Ayu Putu (Thawalib: Jurnal Kependidikan Islam, 2025)
Teachers’ work motivation is influenced by intrinsic and extrinsic factors, school leadership, quality management, and working conditions, all of which affect teacher performance and the overall quality of learning. This study aims to analyse the influence of implementing school quality management system regulations on teachers’ work motivation, enhancing engagement, satisfaction, and sustainable professional performance. A correlational quantitative research method was employed, with the sample consisting of principals, teachers, and educational staff. Data were collected through questionnaires and analysed using SmartPLS to conduct validity, reliability, and t-tests. The results demonstrate that convergent validity was assessed through outer loading and AVE to evaluate the extent to which indicators accurately represent their corresponding latent constructs. The outer loading values for SQMS ranged from 0.791 to 0.890, and for TWM, from 0.866 to 0.922, all of which exceeded 0.70, indicating valid indicators. The AVE values, 0.721 and 0.796, respectively, were above 0.50, confirming convergent validity. Discriminant validity, as demonstrated by cross-loading, showed that each indicator loaded higher on its respective construct than on the others, ensuring a clear distinction between SQMS and TWM. Reliability was assessed using Cronbach’s Alpha and Composite Reliability, both of which demonstrated high consistency (>0.87). The t-test indicated that SQMS has a significant influence on TWM (t = 15.217; p < 0.05), confirming that the implementation of the school quality management system positively supports teachers’ motivation. Conclusion: SQMS has a significant positive influence on teachers’ motivation, enhancing autonomy, competence, self-confidence, participation, professionalism, and the sustainable quality of education